Changes in glycosphingolipid levels in plasma and cerebrospinal fluid of individuals with Lysosomal Free Sialic Acid Storage Disorder - Marya S. Sabir; Lynne Wolfe; David R. Adams; Carla Ciccone; Forbes D. Porter; William A. Gahl; Marjan Huizing; Frances M. Platt; May Christine V. Malicdan (Rare)
Lysosomal free sialic acid storage disorder (FSASD) is a rare, multisystem disease caused by biallelic pathogenic variants in SLC17A5, encoding the lysosomal transmembrane sialic acid exporter, sialin. Defective sialin function leads to sialic acid accumulation in lysosomes, contributing to neurodegeneration. While glycosphingolipid (GSL) metabolism is altered in other lysosomal storage disorders, its role in FSASD remains poorly understood, especially due to the restricted availability of biospecimens. This study investigated GSL levels in FSASD plasma and cerebrospinal fluid (CSF) using two normal-phase high-performance liquid chromatography assays. In plasma, GM1a was significantly elevated, while GM2 was decreased, with no significant alterations in other GSL species. In CSF, total GSLs, GM1a, GM3, GD3, GD1a, and GD1b were significantly elevated compared to comparison samples. These results reveal dysregulated GSL metabolism and suggest the potential of gangliosides as biomarkers. Further research is warranted to elucidate the biological implications of these alterations and their contributions to FSASD pathogenesis.